Brain Metastases in Gynaecologic Cancer: A Retrospective Cohort Study Evaluating Treatment Outcomes, Prognostic Factors, and Overall Survival - Carly M. Cooke; M. Ege Babadagli; Hillary Wilson; Vimoj J. Nair; Krystine Lupe; Shawn Malone; Laura Burgess; Wylam Faught; Rajiv Samant; Tien Le (Current Oncology)
(1) Background: The objectives of this study were to assess survival of patients with a diagnosis of brain metastases secondary to gynaecologic malignancy and the impact of clinicopathological factors on prognosis in this population. (2) Methods: A retrospective cohort of patients with gynaecologic cancers diagnosed with brain metastases treated with radiation at a tertiary care centre from 1 January 2004 until 30 September 2023 was studied. Kaplan–Meier method and log-rank test were used to evaluate survival, and cox regression was used to identify significant predictive factors of survival. (3) Results: In total, 103 patients were included in this study. Median age at diagnosis of brain metastases was 59 (range 30–94). Median survival time following diagnosis of brain metastases was 3.6 months (range 0.4–183.8). Survival was significantly longer for patients treated with surgery combined with radiation compared to radiation alone and with stereotactic radiosurgery (SRS) compared to whole brain radiation therapy (WBRT). Cox regression revealed that primary ovarian malignancy, extracranial disease at diagnosis, and ≥3 brain metastases were associated with poorer prognosis, and complete response to prior treatment was associated with more favourable prognosis. (4) Conclusions: Data from this study will assist in providing evidence-based prognostic information to patients with gynaecologic malignancy diagnosed with brain metastases.